Integrating the Philosophy of Tri Hita Karana into Indonesian language material provision - Relin, Institut Hindu Dharma Negeri Denpasar, Binawati, Sariani. Ni Wayan, Rasna, I Wayan, Sudiana, I Gusti Ngurah, (Opción, 2019)
The aim of the study is to investigate the philosophy of Tri Hita Karana into Indonesian language material provision. The design was mixed: in terms of its objective, it was descriptive using a survey technique, while in terms of data collection, it was qualitative. The results of the study showed that Tri Hita Karana philosophy is very relevant to be integrated into Indonesian material provision for first and second grades at primary school. In conclusion, the Indonesian Textbook with the Contextual Approach is appropriate and may be accepted to be used and to be disseminated.